BENTUK INOVASI PADA KLASTER JAMBU GETAS MERAH DI KABUPATEN KENDAL - Mohamad Auzan Rasis; Samsul Ma'rif (Jurusan Perencanaan Wilayah dan Kota, 2016)
Getas guava cluster in Kendal Regency is the central source of getas guava in Central Java Province. Kendal Regency’s getas guava cluster has 4 central production areas, which are Patean District, Pageruyung District, Sukorejo District, and Plantungan District. On every harvest, Kendal Regency’s getas guava always produces plenty of products. Unfortunately, the overproduction has not been utilized by the member of getas guava cluster in Kendal Regency, because many of the products can’t be marketed and thrown away because of rot. The purpose of this writing is to identify innovation form/type of getas guava cluster in Kendal Regency. On this research, the method used is qualitative research, while analysis method is using quantitative descriptive analysis. Based on the research results, getas guava cluster has many potentials to be utilized and the problem that has to be solved. On Kendal Regency’s getas guava cluster, found some innovations that has been done, namely product innovation, system innovation, process innovation, and marketing innovation. But the innovation on Kendal Regency’s getas guava cluster is categorized as incremental innovation. This causes a not very significant innovation towards the innovation results.